Scaffold selection for tissue engineering in dentistry - Farinawati Yazid; Nurmimie Abdullah; Nur Atmaliya Luchman; Shahrul Hisham Zainal Ariffin; Rohaya Megat Abdul Wahab (Pusat Perubatan Universiti Kebangsaan Malaysia, 2020)
Tissue engineering aims to restore lost, damaged, diseased or defective tissues in the human body using engineered or regenerated products. The advancement of tissue engineering has given a promising opportunity for better clinical practice in treating dental patients especially in the fields of endodontic, bone and periodontal tissue as well as whole tooth regeneration. In this review, we briefly summarise the possible selection criteria of scaffolds for potential tissue engineering applications in dentistry. Biochemical and physical properties, as well as scaffolding approaches involved in the selection of an ideal scaffold for dental tissue engineering, are also discussed in this review. This review also discussed major applications of tissue engineering in the dentistry field, which can create a paradigm for future studies of tissue regeneration by using selected cells and scaffolds as an alternative treatment in dentistry.